2019
DOI: 10.3892/ol.2019.10674
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑101 modulates cisplatin chemoresistance in liver cancer cells via the DNA‑PKcs signaling pathway

Abstract: Due to the high incidence of liver cancer, chemoradiotherapy and prognosis of liver cancer are a primary focus of medical research. microRNAs (miRNAs/miRs) serve crucial roles in resistance to chemotherapy and radiotherapy. The aim of the present study was to investigate the effects of miR-101 on the chemotherapeutic efficacy of cisplatin (CDDP) in liver cancer. First, human liver cancer cells (HepG2) were transfected with a miR-101 mimic or miR-101 inhibitor to bidirectionally regulate the expression of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…MiR-101 overexpression augments cytotoxicity and reduces chemoresistance to chemotherapeutic reagent cisplatin (CDDP) in liver cancer cell line HepG2 cells through inhibiting the DNA-PKcs/Akt/NF-κB signaling pathway. 30 Circular RNA circVAPA is upregulated and exerts oncogenic properties by sponging miR-101 in colorectal cancer. 31 MiR-101 has been reported to inhibit Nrf2 expression from impeding breast cancer cell proliferation and enhancing their sensitivity to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-101 overexpression augments cytotoxicity and reduces chemoresistance to chemotherapeutic reagent cisplatin (CDDP) in liver cancer cell line HepG2 cells through inhibiting the DNA-PKcs/Akt/NF-κB signaling pathway. 30 Circular RNA circVAPA is upregulated and exerts oncogenic properties by sponging miR-101 in colorectal cancer. 31 MiR-101 has been reported to inhibit Nrf2 expression from impeding breast cancer cell proliferation and enhancing their sensitivity to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB pathway is involved in the regulation of the inflammatory and immune responses (58) and miR-101 regulates the NF-κB pathway in several diseases. For example, miR-101 attenuates cisplatin chemoresistance by reducing NF-κB signaling in hepatocarcinoma (59) and miR-101 silencing facilitates the pathogenesis of neuropathic pain by promoting NF-κB activity (60). In the present study, the expression of NF-κB-related proteins in SLE PBMCs was markedly decreased following miR-101-3p overexpression, indicating that miR-101-3p may be involved in the development of SLE via its inhibition of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…19 Chai et al reported that overexpression of miR-101 enhanced the sensitivity of liver cancer cells to cisplatin via inhibiting the activation of DNA-PKcs signaling pathway. 20 Sun et al indicated that inhibition of miR-4262 reduced PTX resistance in lung cancer cells. 21 In addition, evidences have been shown that miR-153 functioned as a tumor suppressor in several cancers including lung cancer, acute lymphoblastic leukemia and breast cancer.…”
Section: Discussionmentioning
confidence: 99%